2022
DOI: 10.3390/s22134981
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Horse Locomotion Modifications Due to Training with Inertial Measurement Units: A Proof-of-Concept

Abstract: Detecting fatigue during training sessions would help riders and trainers to optimize their training. It has been shown that fatigue could affect movement patterns. Inertial measurement units (IMUs) are wearable sensors that measure linear accelerations and angular velocities, and can also provide orientation estimates. These sensors offer the possibility of a non-invasive and continuous monitoring of locomotion during training sessions. However, the indicators extracted from IMUs and their ability to show the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…By monitoring specific accelerometric variables, this observational exploratory field study identified several kinematic changes in eventing horses between and at the jumps across 4*‐cross‐country tests. This complements two recent studies using another inertial measurement unit and examining sport horses before and after their training sessions 15,21 . New candidates for kinematic characteristics during competitive exercise, such as the maximal strike power at the jumps, were identified in our study to be associated with an altered jumping profile and potentially indicating the onset of fatigue.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…By monitoring specific accelerometric variables, this observational exploratory field study identified several kinematic changes in eventing horses between and at the jumps across 4*‐cross‐country tests. This complements two recent studies using another inertial measurement unit and examining sport horses before and after their training sessions 15,21 . New candidates for kinematic characteristics during competitive exercise, such as the maximal strike power at the jumps, were identified in our study to be associated with an altered jumping profile and potentially indicating the onset of fatigue.…”
Section: Discussionsupporting
confidence: 65%
“…This complements two recent studies using another inertial measurement unit and examining sport horses before and after their training sessions. 15,21 New candidates for kinematic characteristics during competitive exercise, such as the maximal strike power at the jumps, were identified in our study to be associated with an altered jumping profile and potentially indicating the onset of fatigue.…”
Section: Discussionmentioning
confidence: 87%
“…Locomotion pattern modifications were detected before and after training sessions in horses. Among the kinematic indicators evaluated, indicators comparing gait cycle kinematics (Pearson’s correlation coefficients and root mean square deviations) and estimating movement smoothness (spectral arc length) indicated changes following training [ 87 ].…”
Section: Horse–rider Interaction and Imusmentioning
confidence: 99%